Isolation of Rhizosphere Bacteria That Improve Quality and Water Stress Tolerance in Greenhouse Ornamentals - Nordstedt, Nathan P.; Jones, Michelle L. (Frontiers in Plant Science, 2020)
Water deficit stress is a major contributor to the loss of ornamental crop value due to its negative effects on plant growth and flowering. In addition, post-production water stress can reduce the photosynthetic capacity of plants, negatively impacting crop quality at retail and in the consumer’s home and garden. While the application of microbe-containing biostimulant products can increase stress tolerance and crop quality, the success of most commercially available biostimulants in greenhouse production systems is inconsistent. To identify beneficial bacteria with consistent biostimulant activity in greenhouse ornamentals, our study isolated bacteria from the rhizosphere of water stressed greenhouse ornamentals. Five species of popular ornamentals were obtained from 15 different commercial greenhouse facilities and then subjected to three cycles of water stress. Over 1,000 bacterial isolates were collected from the rhizosphere and screened in vitro for osmoadaptability and 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity. Eighty selected isolates were evaluated in a high-throughput greenhouse trial for their ability to increase plant size and flower number of water-stressed Petunia × hybrida. Ten bacterial strains selected from the high-throughput trial were then evaluated in a greenhouse validation trial for their ability to increase plant growth and to mitigate the reduction in photosynthetic parameters of water stressed P. hybrida and Pelargonium × hortorum. Application of certain bacteria increased plant size in both species and flower number of P. hybrida after recovery from water stress when compared to untreated water stressed plants. In addition, bacteria application increased the chlorophyll fluorescence parameters including quantum yield and efficiency of photosystem II (PSII) and electron transport rate (ETR), while decreasing the extent of electrolyte leakage during water stress and recovery. Overall, this study identified bacterial strains that can increase tolerance to and recovery from water stress in two commercially important ornamental crop species.